Variáveis definidoras dos valores dos imóveis estudo de caso - Santa Maria - RS. - Brenner, Mara Lúcia (2006)
The objective of this paper is provide a general model for the appraisal of real estate properties, to be available to engineers, city officials, and other real estate related professionals. The basis for this research and paper has been the absence of such data"in the current city records, and our belief that this information can be invaluable to a successful appraisal job. This subject has been postponed even during times of implementation of new city statutes, building codes, and new city plans. Based upon the sample in which this research is founded, one can better understand the pricing trend of the real estate market in the last few years. Via regression models we found that an equation in which variables such as total area, private area, month, age, number of bedrooms, parking, distance to a geodesic mark, and the distance to a known street of town ("Calçadão"), are significant information in the appraisal of residential apartments in the city of Santa Maria. The methodology herein presented may be applied not only to large projects but also to the appraisal of small to mid-size projects, where more precision may be required.